2001
DOI: 10.1055/s-2001-16423
|View full text |Cite
|
Sign up to set email alerts
|

Bevölkerungsbezogenes Gesundheitsmonitoring in Bayern mit computerassistierten Telefoninterviews

Abstract: From June 1999 until May 2000, 2051 computer-assisted telephone interviews concerning health and health related behaviours were assessed in Bavarian households. The aim of the study was the evaluation of the validity and representativity of this data by a comparison of selected variables from the Bavarian Mikrozensus-survey 1999. The distribution patterns of the marital status, the size of the households, the gainful employment, the household-netto-income, the school qualification and of the smoking status cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Advantages of CATI are time management both for the participants and for the initiators of the study, in the interview management, within the complexity of the questionnaire and within the data quality achieved. Like common in surveys, participants of the present CATI-study showed a shift to higher social classes as refl ected by a higher school graduation [12,14] . The socio-economic characteristics of the participants indicate that members of higher social classes are more likely to participate.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Advantages of CATI are time management both for the participants and for the initiators of the study, in the interview management, within the complexity of the questionnaire and within the data quality achieved. Like common in surveys, participants of the present CATI-study showed a shift to higher social classes as refl ected by a higher school graduation [12,14] . The socio-economic characteristics of the participants indicate that members of higher social classes are more likely to participate.…”
Section: Discussionmentioning
confidence: 57%
“…We achieved a response of 47 % . International studies describe response rates ranging from 23 % [11] , to 57 % [12] and up to 67 % or 60 % [6] . Causes for this divergence are to be found in regional variances.…”
Section: Discussionmentioning
confidence: 99%
“…Da ein Vergleich demografischer Merkmale bereits an anderer Stelle mit dem Mikrozensus 1999 vorgenommen wurde [10], soll der entsprechende Vergleich mit den Daten des Bundes-Gesundheitssurveys im Folgenden nur skizziert werden.…”
Section: Demografische Merkmaleunclassified
“…Ziel war die Überprüfung der Übereinstimmung der Ergebnisse beider Erhebungen. Ergänzend erfolgte die Evaluation der Datenrepräsentativität durch einen Vergleich ins-besondere demografischer Merkmale mit dem Mikrozensus 1999 [10]. Dabei zeigte sich, dass das Verteilungsmuster des Familienstandes, der Haushaltsgröße, der Erwerbstätigkeit, des Haushaltsnettoeinkommens sowie des Schulabschlusses gut mit denen des Mikrozensus übereinstimmte.…”
Section: Introductionunclassified